The Importance of Occupational Health Service in the Era of VUCA and the Dissemination of Related Research Results - Mansyur, Muchtaruddin (UI Scholars Hub, 2023)
Worldwide have been facing the era of dynamic life with the rapidly changing global situation for decades. This era is colored by volatility, uncertainty, complexity, and ambiguity (VUCA) situation that is aggravated by the COVID-19 pandemic. We have all experienced the VUCA situation with the COVID-19 Pandemic that has lasted over 2 years. The United Nations Development Programme (UNDP)1 report should be a common reference for dealing with situations that are not just uncertain but also called “uncertainty complexes”. So-called because its dimensions take on a new form that has never been seen before in human history. The complexity of such uncertainties includes global instability and Anthropocene inequality, the acceleration of social transformation to cope with global pressures, and widespread and intensive polarization1. The experience of facing the VUCA era and the COVID-19 Pandemic can be a provision to turn these uncertainties into expected ones. One such opportunity is made possible by keeping productive communities through the strengthening of occupational health services. Strengthening occupational health to improve the productive age group health status is a driver of productivity through efforts to prevent and control occupational and environmental health hazards2. Better occupational health services with the occupational medicine best practices are a potent strategy to overcome the raised new emerging and re-emerging potential health hazards. The shifting of the workplace and working hours across time zones are good examples of new emerging potential health hazards. The workplace shifts from the office to “working from home” or “working from anywhere” has become a common thing to implement in various sectors. Changes in the workplace lead to potential health hazards and consequent changes, including ergonomics and psycho-social health risks. The ergonomic risks of working from home and teleworking lead to an increase in work-related musculoskeletal disorders3,4. The psycho-social climate at work also changed. Studies showed psycho-social changes in the workplace during the COVID-19 Pandemic that also cause mental and emotional disorders5. From these studies, we can see that there are changes in Occupational Health risks that need to be controlled. The spread of COVID-19 in the workplace is another form of an unavoidable increase in biological risk amid efforts to defend the economic situation from uncertain threats. Controlling the spread of COVID-19 in the workplace is a good example of the importance of occupational health services6. In the VUCA era, the Occupational Health approach should be continuously improved and promptly adjusted in times to make more effective responses. Research and development of occupational medicine good practices are essential in occupational health services. Then, research results and good practices developed should be published and shared to gain broader beneficiaries. To contribute further, the Indonesian Occupational Medicine Association in collaboration with the Universitas Indonesia and Krida Wacana Christian University-Jakarta, published a journal entitled Occupational & Environmental Journal of Indonesia. We expect this journal to increase the contribution of researchers in the field of health, especially occupational medicine and the environment, through their published research.